Pengontrolan Tandon Air Berbasis IoT Menggunakan Node MCU 8266 - Salahuddin; Yusman; Zamzami; Bakhtiar; Sayed Munazzar; Muhammad Nasir (Jurnal Serambi Engineering, 2024)
The control and monitoring of the water tank, located on the third floor of the building, continues to face problems related to the filling process and limited monitoring. Water continues to enter the tank unnoticed, resulting in energy wastage. This study aims to create a framework that can monitor the water level in the tank of a three-storey building using Internet of Things (IoT) technology. The tank's water level monitoring system uses a JSN-SR04T ultrasonic sensor to collect water level data, with a Node MCU serving as the microcontroller. The system can monitor water levels from 0% to 100%. A reading of 0% indicates that the water is at its minimum level, while 100% indicates that the water tank has reached its maximum capacity. The system created can monitor excessive water consumption at each level using a flow meter sensor. The Virtuino application can stop the water flow by pressing the ON button, which activates the relay in the design model and stops the water flow at any desired level. The water pump will start to fill the reservoir until it reaches the desired level set by the user based on their needs.